“Dark commercial patterns” o “Patrones comerciales oscuros” en el Perú: Comentarios sobre su licitud y evaluación en materia de protección al consumidor - Olano Rodríguez, Karina Leticia (2024)
This article explores dark patterns in commerce, including their definition, key elements, and modalities. These practices are increasingly relevant in virtual commerce channels, raising concerns among competent bodies regarding their potential infringement on consumer choice freedom. In Peru, consumer protection regulations could empower the National Institute for the Defense of Competition and the Protection of Intellectual Property (Indecopi) to apply coercive, aggressive, or deceptive commercial methods to sanction such practices. Given the limited legal precedent in Peru, it’s crucial to examine comparative regulation and jurisprudence to better understand how to resolve these cases, aiming to protect consumer rights without unjustifiably restricting commercial innovation. Finding a balance that allows providers to exercise their right to private initiative and promote sales through accurate information in their publications is essential.